The malignant potential of ordidinary condyloma and other related precancerous lesions of the uterine cervix - Lindeque, B. G.(Barend Gerhardus),1953- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.D.) -- University of Stellenbosch, 1989.